O ensino de ciências nos anos iniciais do ensino fundamenta l: um estudo das narrativas produzidas no estágio supervisionado em um curso de Pedagogia no interior do Estado do Espírito Santo - Guisso, Sandra Maria (2018)
The Science teaching in the early years of elementary education has been widely discussed, because it has implications for the children’s citizenship development. Thus, we seek to identify and analyze, through the supervised trainee, the challenges and the main methodological approaches mobilized by the teachers of the Pedagogy course, for the teaching of natural Sciences in the initial years of elementary education. In addition, we seek to know, through the Pedagogical Project of the Pedagogical Course, the Supervised Curricular trainee course and the subjects related to the Sciences teaching in the Pedagogy course, as well as the pedagogical proposals regarding the teaching of science, public schools that were part of the study. We carried out a qualitative research and the narrative as a methodological outline. For the production of data we considered the trainees’ oral and written narratives, field diary, as well as documents referring to the pedagogical project of the Pedagogy Course of the institution researched and the curricular proposals of the municipalities that constitute the field of training. The data analysis process was based in the Discursive Textual Analysis (ATD), which contributed to highlight that one of the main challenges for Science Education in the initial years refers to the conception of literacy in this educational stage, especially in the first three years of the elementary school, which is strongly associated with the Portuguese language and Mathematics. The documentary analyzes revealed that the Pedagogy course offers a longer time dedicated to the subjects of superior Science than the one found in the literature. The students´ classes showed that it is possible to develop Science teaching through methodologies used routinely during classes, but, highly formative, when elaborated and developed in a context of scientific literacy conceived in a broad and wide way